Rancang Bangun Pengaman Pintu Menggunakan RFID Dengan Mikrokontroler Atmega 328 - Mardiono, Djoko Anwar; Nanra, Suwadi; Rican, Duma (Penerbit Goodwood, 2023)
Purpose: This study aims to design and develop a house door safety device using an RFID (Radio Frequency Identification) sensor integrated with an ATmega 328 microcontroller. The device is intended to offer an easy-to-use, affordable, and practical solution to enhance comfort and security in opening house doors without the inconvenience of carrying multiple physical keys. Methodology/approach: The development process involved integrating an RFID sensor module with an ATmega 328 microcontroller as the main control unit. When a registered RFID tag card is detected, the microcontroller processes the signal and triggers a solenoid mechanism to unlock the door. The device is powered by a primary electrical source and supported by a rechargeable battery backup to ensure continuous operation. Testing procedures were conducted to verify the device’s performance against the design specifications. Results/findings: Experimental testing showed that the device successfully detected authorized RFID tags and reliably unlocked the door using the solenoid mechanism. The backup battery system maintained functionality even during power outages, ensuring uninterrupted security. Conclutions: The proposed RFID-based house door safety device with an ATmega 328 microcontroller provides a practical, low-cost, and effective solution for residential door security. It offers improved user convenience compared to traditional key-based systems. Limitations: The system currently operates only with pre-registered RFID tags and has limited range and scalability. Further development is needed for remote access, enhanced encryption, and integration with smart home systems. Contribution: This research contributes to the field of low-cost smart home security solutions by demonstrating an effective prototype of an RFID-based door safety device, which can serve as a foundation for future advancements in intelligent access control systems.